2012
DOI: 10.17816/kmj1546
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculin diagnostics in pulmonary tuberculosis combined with HIV-infection

Abstract: Aim. To evaluate the sensitivity to tuberculin in patients with infiltrative pulmonary tuberculosis in combination with an infection, caused by the human immunodeficiency virus (HIV), using various different tests. Methods. Examined were patients with infiltrative pulmonary tuberculosis with HIV infection (134 patients, the main group) and without HIV infection (100 patients, control group). Tuberculin diagnostics included an intradermal Mantoux test with 2 tuberculin units, the skin prick te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Four studies 25,27,32,40 performed head-to-head comparisons of Diaskintest vs TST 5mm and IGRA in the same study. Study populations enrolled in studies included HIVinfected individuals 33,38,44,49 (346 adults, 23 children)) and children under 18 (N=3,803) (Table 1). 21,[25][26][27][28][29][30][31][32][34][35][36]41,48 Approximately half of the HIV-infected cohorts had a CD4 count lower than 200 cells/mm 3 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies 25,27,32,40 performed head-to-head comparisons of Diaskintest vs TST 5mm and IGRA in the same study. Study populations enrolled in studies included HIVinfected individuals 33,38,44,49 (346 adults, 23 children)) and children under 18 (N=3,803) (Table 1). 21,[25][26][27][28][29][30][31][32][34][35][36]41,48 Approximately half of the HIV-infected cohorts had a CD4 count lower than 200 cells/mm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…33,38 Proportion BCG vaccinated was reported in 4 studies, and ranged from 93-100%. 25,27,28,44 Diaskintest threshold for positivity varied and included any skin induration (Diaskintest AI ) according to national guidance 50 or 5mm (Diaskintest 5mm ). Studies used PPD-L TST previously shown bioequivalent to PPD-RT23; 51,52 5mm (TST 5mm ) induration denoted positivity, and 1-5 mm indeterminate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations